2010
DOI: 10.1099/ijs.0.021048-0
|View full text |Cite
|
Sign up to set email alerts
|

Hwanghaeicola aestuarii gen. nov., sp. nov., a moderately halophilic bacterium isolated from a tidal flat of the Yellow Sea

Abstract: A moderately halophilic Gram-staining-negative bacterium, designated strain Y26T, was isolated from a tidal flat of Taean coast in South Korea. Cells were strictly aerobic, motile cocci with a single flagellum and showed catalase- and oxidase-positive reactions. Growth of strain Y26T was observed at 15–35 °C (optimum 25–30 °C), pH 6.0–8.0 (optimum pH 6.5–7.5) and with 1.5–6.0 % (w/v) NaCl (optimum 2.0–3.0 %). The predominant fatty acids were C18 : 1 ω7c (66.2 %), C16 : 0 (12.4 %) and C10 : 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…The fatty acid profiles of strain X12M-4 T and M. alkaliphilus CGMCC 1.7698 T are shown in . The cellular fatty acid profile obtained in this study for M. alkaliphilus CGMCC 1.7698 T was similar to that in the original description (Lee et al , 2007) and reported in other publications (Kim et al , 2010; Lee et al , 2007; Yoon et al , 2009) in terms of major fatty acids, although there were differences in proportions, which might be due to the different culture conditions. Strain X12M-4 T had a fatty acid profile similar to that of M. alkaliphilus CGMCC 1.7698 T under the same cultivation conditions ().…”
supporting
confidence: 88%
“…The fatty acid profiles of strain X12M-4 T and M. alkaliphilus CGMCC 1.7698 T are shown in . The cellular fatty acid profile obtained in this study for M. alkaliphilus CGMCC 1.7698 T was similar to that in the original description (Lee et al , 2007) and reported in other publications (Kim et al , 2010; Lee et al , 2007; Yoon et al , 2009) in terms of major fatty acids, although there were differences in proportions, which might be due to the different culture conditions. Strain X12M-4 T had a fatty acid profile similar to that of M. alkaliphilus CGMCC 1.7698 T under the same cultivation conditions ().…”
supporting
confidence: 88%
“…It has long been known that tidal flats contain a wealth of valuable biological resources such as micro-organisms and marine animals and play important roles in the restoration of coastal ecosystems and nutrient cycling (Winberg et al , 2007; Jin et al , 2012; Math et al , 2012). In the course of studies investigating micro-organisms inhabiting tidal flats, we have isolated and characterized many novel bacterial species (Kim et al , 2010; Jin et al , 2011; Lee et al , 2011; Jeong et al , 2013a, b). Here, we describe the taxonomic characterization of a novel species belonging to the genus Shewanella isolated from a tidal flat of the South Sea in South Korea.…”
mentioning
confidence: 99%
“…Members of the family Rhodobacteraceae are metabolically and physiologically diverse and occupy a wide range of niches in various habitats, such as seawater, saline, sediments, sea ice, microbial mats, seaweeds and marine animal tissues. Several genera, including Maribius (Choi et al , 2007), Marivita (Hwang et al , 2009), Mameliella (Wang et al , 2010), Roseovarius (Zheng et al , 2010) and Hwanglaeicola (Kim et al , 2010), have been described in the last 4 years. In this study, a novel and slightly halophilic strain, designated KAUST-100406-0324 T , was isolated from the sediment near a deep-sea brine pool in the Red Sea and characterized using a polyphasic approach.…”
mentioning
confidence: 99%